Transfer and migration of polycyclic aromatic hydrocarbons in soil irrigated with long-term wastewater - Song, Cui; Qiang, Fu; Tianxiao, Li; Dong, Liu; Yifan, Li; Min, Wang (International Journal of Agricultural and Biological Engineering, 2016)
In order to investigate the transfer and migration behavior of polycyclic aromatic hydrocarbons (PAHs) in soil with long-term wastewater irrigation, Groundwater Ubiquity Score (GUS) and fugacity method were respectively used to assess the potential entry into the groundwater and transfer capacity of PAHs. The results of assessment using GUS show that there is significant correlation between the GUS and organic carbon sorption coefficient (KOC) for PAHs and a simple assessment method with KOC was referred to evaluate contamination of groundwater. Applying fugacity method, evaluation results of transfer and migration of PAHs in soil suggest that the PAHs accumulation in the soil through long-term wastewater irrigation could be re-volatilized as secondary emission sources to atmosphere for the Low Molecular Weight (LMW) PAHs, in contrast to High Molecular Weight (HMW) PAHs for which the soil remains a sink that could absorb more PAHs. The net volatilisation flux was 0.39 g/d in upland and 0.32 g/d in paddy for LMW Nap (Naphthalene), and 0.97×10-3 g/d in upland and 0.37×10-3 g/d in paddy for LMW Phe (Phenanthrene). The net deposition was 0.72×10-4 g/d in upland and 0.10×10-3 g/d in paddy for HMW Fla (Fluoranthene), and 0.22×10-4 g/d in upland and 0.20×10-4 g/d in paddy for HMW Bap (Benzo[a]pyrene). Sensitivities of the model estimates to input parameters were tested, and the sensitivity coefficient was defined for the test. The most influential parameters were the volumes of the air, water, and organic carbon fractions in soil and the thickness of the soil.Keywords: wastewater irrigation, polycyclic aromatic hydrocarbons, transfer and migration, groundwater contamination, groundwater ubiquity scoreDOI: 10.3965/j.ijabe.20160905.2528Citation: Cui S, Fu Q, Li T X, Liu D, Li Y F, Wang M. Transfer and migration of polycyclic aromatic hydrocarbons in soil irrigated with long-term wastewater. Int J Agric & Biol Eng, 2016; 9(5): 83－92.